A topology control-based self-organisation in wireless mesh networks. (6th November 2008) - Prodan, Ante; Mirchandani, Vinod; Debenham, John
An algorithm for self-organisation that assigns the channels intelligently in multi-radio wireless mesh networks (MR-WMN) is important for the proper operation of MR-WMN. The aim of the self-organisation algorithm is to reduce the overall interference and increase the aggregate capacity of the network. In this paper, we have first proposed a generic self-organisation algorithm that addresses these two challenges. The basic approach is that of a distributed, light-weight, cooperative multiagent system that guarantees scalability. Second, we have evaluated the performance of the proposed self-organisation algorithm for two sets of initialisation schemes. The initialisation process results in a topology control of MR-WMN by way of spatial distribution of connectivity between the mesh nodes. The results have been obtained for realistic scenarios of MR-WMN node densities and topologies. We have shown in addition the need to develop non-transmit power control based algorithms to achieve a further increase in system capacity.